PRIVATIZATION OF AGRICULTURE AFFECTED BY FOREIGNERS - Avramović, Nenad Momčilo; Stanković, Marko (Economics of Agriculture, 2020)
The collapse of socialism changed the global picture of the world order and on international plan shifted most of the ex-communist countries of Europe towards Euro-Atlantic integration and membership in the European Union. The economic and social transition of most post-socialist states under the influence of Euro-Atlanticists and domestic pro-Western reformers, is taking place under Washingtons consensus. The proposal of international mentors was the urgent privatization, liberalization and decentralization of the economy and society. The aim of the paper is to analyze the privatization of Serbian agriculture according to the shock model, both from the aspect of the application of regulations and the work of institutions, as well as the evaluation of the success of the procedure and privatization effects. Privatization of agricultural enterprises in Serbia has shown numerous weaknesses, which manifest in the work of institutions, inadequate strategy and vision, and in economic terms of stagnation of livestock breeding, reduction of the number of agricultural holdings and increase of unemployment. In this context, the experiences of Germany and China and some European Union countries were presented, which in the choice of transition path were guided primarily by their state and national interests.